2007
DOI: 10.1021/jm070189q
|View full text |Cite
|
Sign up to set email alerts
|

Novel Vanilloid Receptor-1 Antagonists:  1. Conformationally Restricted Analogues oftrans-Cinnamides

Abstract: The vanilloid receptor-1 (VR1 or TRPV1) is a member of the transient receptor potential (TRP) family of ion channels and plays a role as an integrator of multiple pain-producing stimuli. From a high-throughput screening assay, measuring calcium uptake in TRPV1-expressing cells, we identified an N-aryl trans-cinnamide (AMG9810, compound 9) that acts as a potent TRPV1 antagonist. We have demonstrated the antihyperalgesic properties of 9 in vivo and have also reported the discovery of novel, orally bioavailable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…In our efforts to identify a TRPV1 antagonist clinical candidate, we synthesized several novel series of molecules representing various chemotypes ( Xi et al, 2005;Ognyanov et al, 2006;Norman et al, 2007;unpublished data) and evaluated their ability to block various modes of TRPV1 activation. AMG 517 inhibited capsaicin, pH 5, and heat-induced 45 Ca 2ϩ uptake into cells expressing TRPV1 with IC 50 values of 1 to 2 nM (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our efforts to identify a TRPV1 antagonist clinical candidate, we synthesized several novel series of molecules representing various chemotypes ( Xi et al, 2005;Ognyanov et al, 2006;Norman et al, 2007;unpublished data) and evaluated their ability to block various modes of TRPV1 activation. AMG 517 inhibited capsaicin, pH 5, and heat-induced 45 Ca 2ϩ uptake into cells expressing TRPV1 with IC 50 values of 1 to 2 nM (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After evaluation of TRPV1 antagonists representing various chemotypes Xi et al, 2005;Ognyanov et al, 2006;Norman et al, 2007;unpublished data) for potency, selectivity, plasma half-life, effects in the capsaicin-induced flinch model, and efficacy in models of inflammatory pain, we identified AMG 517 as a potential drug for the management of pain in humans. Here, we describe the characterization of AMG 517 and the data set leading to its selection as a clinical candidate.…”
Section: Amino]carbonothioyl)amino)methyl]-2-fluorophenyl)meth-mentioning
confidence: 99%
“…In the present work, the reactions of tetramer and trimer with 1,4-benzodioxan-6-amine used in pharmaceutical applications such as antagonists [35], cytotoxic molecules for inhibitory activity against human breast cancer cells [36] were investigated in order to determine their nucleophilic substitutions pathway and compare to cyclotri-and tetraphosphazenes.…”
Section: Introductionmentioning
confidence: 99%
“…15) Literature revealed that the some substituted pyrimidines act as novel and potent TRPV1 antagonists for the treatment of hyperalgesia. 16,17) In view of these references, the synthesis of a new series of 2,4,6-trisubstituted pyrimidines are now reported. The desired target compounds (5a-m) were prepared from the 1,3-diarylpropenones (3a-m) 18,19) and guanidine (4) by refluxing them together in a basic alcoholic media (Chart 1).…”
Section: Regular Articlementioning
confidence: 99%